An IMU-based sensor network to continuously monitor rowing technique on the water - Tessendorf, B.; Gravenhorst, F.; Arnrich, B.; Tröster, G. (Proceedings of the Seventh International Conference on Intelligent Sensors, Sensor Networks and Information Processing (ISSNIP 2011), 2011)
In the sport of rowing athletes and coaches are concerned with optimizing a rower`s technique in order to improve rowing performance. In this paper, we present the design and real-world evaluation of a sensor network approach to support improving the rower`s performance. In cooperation with professional rowing teams, we found that a network of inertial measurement units (IMUs) is well suited to continuously and unobtrusively monitor important indicators relating to rowing technique. In a feasibility study with 5 participants we first investigated the optimal sensor setup, and in the final setup we attached 3 IMUs to the oars and the boat. From 18 participants (including both ambitious amateurs and world-class rowers) we recorded both training and racing sessions which each consisted of 1000m rowing.We present 4 rowing technique indicators for all 18 participants. Using the example of two world-class rowers we demonstrate in detail how sensor networks support the iterative process of optimizing the individual rowing technique.